Niche models as a tool to inform restoration and conservation strategies: the case of Jubaea chilensis (palm, Arecaceae) and its seed disperser Octodon degus (rodent, Octodontidae) - Núñez-Hidalgo, Ignacio; Fleury, Marina; Bustamante, Ramiro O. (Frontiers in Forests and Global Change, 2023)
1. Biotic interactions are a crucial component of the plant regeneration process, which has been traditionally studied at more local scales, providing the tools for planning and decision-making. Studies showing the signature of species interactions at coarser spatial scales contrasting with animal-plant interactions at fine scales have been scarce. 2. This study aimed at integrating an approach, over both biogeographic and local scales, by testing two endemic species of Mediterranean central Chile: the relict and southernmost threatened Chilean palm Jubaea chilensis (Chilean palm; Molina; Baillón) and the caviomorph scatter-hoarding rodent Octodon degus (Degu; Molina), on which this palm currently relies for seed dispersal. 3. Integrating Geographic Information Systems and Ecological Niche Modeling, the intensity of seed-rodent interactions from a territorial perspective was evaluated in the range of the palm, at a biogeographic scale, identifying areas with greater or lesser potential for seed-rodent interactions; and in local populations, incorporating a variety of environmental factors that might affect palm regeneration. 4. The present results show that the rodent (Octodon degus) may play a role in Chilean palm (Jubaea chilensis) seed dispersal and seed establishment, since; Chilean palm regeneration is higher in areas where both species co-occur. At a local scale, a prominent overlap between palm seedlings and degu burrows was also found, which, allied with other abiotic variables such as altitude and topographic humidity, are crucial for successful palm regeneration. 5. Synthesis and applications: Understanding the full extent of animal-plant interactions and how they are affected by habitat perturbation in a wide range will provide essential information for the design of effective conservation and management strategies, such as rewilding based on plant species.